The effects of audio-video instruction in brushing teeth on the knowledge and attitude of young slow learners in Cirebon regency - Yayah Sopianah; Muhammad Fiqih Sabilillah; O. Oedijani (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: Young slow learners are children with special needs who require special attention to satisfy their personal hygiene needs, especially those of dental hygiene since they are particularly susceptible to tooth decay. Changing the knowledge and attitudes of those slow learners can be achieved by a proper method. Purpose: This study aimed to analyze the effects of teaching effective methods of brushing teeth by means of an audio video approach on the knowledge and attitude of young slow learners in Cirebon regency. Methods: This study was quasi-experimental in nature using pre test-post test methods within a two-group design. The sampling technique employed was purposive in nature. The number of young slow learners as respondents in this research totalled 31 individuals. Those children were, subsequently, divided into two groups; Group I containing 16 children, instructed in tooth brushing techniques by means of an audio video method and Group II composed of 15 children who were taught tooth brushing techniques manually. The variables measured consisted of subjects’ knowledge of and attitude towards how to brush teeth most effectively identified by means of a questionnaire, in order that the interval data could be collected. Results: The results of an independent T-test showed there to be significant differences in the mean scores of the knowledge variable and the attitude variable (p = 0.003 and p = 0.000 respectively) between Groups I and II, at that stage of the investigation. Conclusion: It can be concluded that instructional audio-videos on how to brush teeth most effectively can improve both the knowledge and attitude of children with slow learning problems.